THE MEDIATING ROLE OF INNOVATION IN THE RELATIONSHIP BETWEEN INTELLECTUAL CAPITAL AND ORGANIZATIONAL PERFORMANCE: AN EMPIRICAL STUDY ON REGIONAL PUBLIC SERVICE AGENCIES - Heri Susanto; Rosita; Amy Wulandari (STABILITY : Journal of Management and Business, 2025)
This study investigates the influence of intellectual capital (IC) on the performance of Public Service Agencies (Badan Layanan Umum Daerah - BLUD) in the Special Region of Yogyakarta, with innovation acting as a mediating variable. A quantitative approach was employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) on data collected from BLUDs in the specified region. The findings indicate that IC has a positive and significant effect on both BLUD performance and innovation. Furthermore, innovation is confirmed to partially mediate the relationship between IC and performance, with a substantial total effect of IC on performance. These results support the Resource-Based View and Dynamic Capabilities theories, emphasizing the crucial role of intangible resources and innovative capabilities in enhancing public organization performance. Practical implications suggest that BLUDs should prioritize strengthening IC management through human resource development, knowledge systems, and strategic collaborations, while simultaneously fostering a culture of innovation to improve service quality. This research contributes theoretically by confirming the mediation mechanism of innovation in the IC-performance relationship within the public sector context, and offers policy recommendations for optimizing BLUD operations.